Human Extension: An Alternative to Evolutionism, Creationism and Intelligent Design - Sandstrom, Gregory. author. aut Link
XX, 97 p.
Keywords: This book proposes a new angle on the controversy over evolution as a biological theory, creation as a theological/worldview doctrine and evolutionism, creationism and Intelligent Design theory as social ideologies. Rather than presenting a polemic that will enrage or delight one camp or another, this book proposes that a cease-fire is possible.